2003
DOI: 10.1128/aac.47.7.2118-2124.2003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics-Pharmacodynamics of Rifampin in an Aerosol Infection Model of Tuberculosis

Abstract: Limited information exists on the pharmacokinetic (PK)-pharmacodynamic (PD) relationships of drugs against Mycobacterium tuberculosis. Our aim was to identify the PK-PD parameter that best describes the efficacy of rifampin on the basis of in vitro and PK properties. Consistent with 83.8% protein binding by equilibrium dialysis, the rifampin MIC for M. tuberculosis strain H37Rv rose from 0.1 in a serum-free system to 1.0 mg/ml when it was tested in the presence of 50% serum. In time-kill studies, rifampin exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
316
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(337 citation statements)
references
References 30 publications
(26 reference statements)
19
316
1
1
Order By: Relevance
“…Studies in the murine model have demonstrated that increasing the dose of P from 10 to 15 mg/kg increases the anti-TB activity (16), a finding consistent with the concentration-dependent activity of the rifamycins (17)(18)(19). Once-weekly continuation phase regimens based on a 15-mg/kg dose of P are at least as active as twice-weekly RH, but are not as active as daily RH (9).…”
mentioning
confidence: 57%
“…Studies in the murine model have demonstrated that increasing the dose of P from 10 to 15 mg/kg increases the anti-TB activity (16), a finding consistent with the concentration-dependent activity of the rifamycins (17)(18)(19). Once-weekly continuation phase regimens based on a 15-mg/kg dose of P are at least as active as twice-weekly RH, but are not as active as daily RH (9).…”
mentioning
confidence: 57%
“…Rifamycins have durable sterilizing activity against Mycobacterium tuberculosis, and the currently recommended 10 mg/kg dosage of rifampin, the most commonly used rifamycin, is at the low end of the dose-response curve (2)(3)(4)(5)(6)(7)(8)(9). Historically, selection of this rifampin dose seems to have been influenced by cost in the setting of incomplete dose-finding studies (10).…”
mentioning
confidence: 99%
“…During this time, progress has also been made in the quantitative description of both pharmacokinetics (PK) and in vitro pharmacodynamics (PD) of antituberculosis drugs [17], [18], [19]. Mathematical models that arise from a systems approach offer a unique potential to establish quantitative links across multiple biological scales.…”
Section: Tuberculosis Modellingmentioning
confidence: 99%